(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
General objective: To study the efficacy of Ultrasoundguided hydrostatic reduction of intussusception in children with early presentation. Methods: The study group included children aged 03 months to 02 years with early case of intussusception confirmed on ultrasonography. One litre of normal saline bag was suspended at 100 cm height from the patients level. After connecting the saline bag with Foleys catheter introduced in the rectum, gradual distension of colon and retrograde movement of intussusceptum towards the caecum monitored by real time ultrasound.Successful reduction was assumed once mass was disappeared and passage of saline into the small intestine. If 1st attempt failed but there is some movement of the mass was present and child had no abdominal signs, 2nd and 3rd attempts were taken at least 30 min interval. Result: The overall success rate of US-guided hydrostatic reduction of intussusception in children with early presentation was about 90%, with no immediate recurrence and no perforation. Conclusion: Ultrasound guided hydrostatic reduction should be the first line of the treatment in patients with early presentation of intussusceptions aged between 3 months and 2 years old. In cases with failed initial reduction, a second or even third attempt may provide successful reduction. J. Paediatr. Surg. Bangladesh 3(2): 61-64, 2012 (July)